The effect of long-range order on intermolecular interactions in organic semiconductors: zinc octaethyl porphyrin molecular thin film model systems. Issue 41 (10th October 2019) - Kumar, A.; Naumenko, D.; Rossi, G.; Magnano, E.; Nappini, S.; Bondino, F.; Segoloni, E.; Amidani, L.; d'Acapito, F.; Boscherini, F.; Barba, L.; Pace, E.; et al.
Abstract : Influence of the ZnOEP thin film growth procedure on molecular orientation, crystalline molecular packing and on intermolecular interactions. Abstract : In order to optimize the performance of devices based on porphyrin thin films it is of great importance to gain a physical understanding of the various factors which affect their charge transport and light-harvesting properties. In this work, we have employed a multi-technique approach to study vacuum deposited zinc octaethyl porphyrin (ZnOEP) thin films with different degrees of long-range order as model systems. An asymmetrical stretching of the skeletal carbon atoms of the porphyrin conformer has been observed and attributed to ordered molecular stacking and intermolecular interactions. For ordered films, a detailed fitting analysis of the X-ray absorption near edge structure (XANES) using the MXAN code establishes a symmetry reduction in the molecular conformer involving the skeletal carbon atoms of the porphyrin ring; this highlights the consequences of increased π–π stacking of ZnOEP molecules adopting the triclinic structure. The observed asymmetrical stretching of the π conjugation network of the porphyrin structure can have significant implications for charge transport and light harvesting, significantly influencing the performance of porphyrin based devices.